2008
DOI: 10.22488/okstate.18.100367
|View full text |Cite
|
Sign up to set email alerts
|

An Application of High Fidelity FTDs for Ab Initio Pilot Training: The Way Ahead

Abstract: Decreases in simulation costs and increases in aircraft training costs led to the need for further investigation into the application of simulation-based training. Researchers conducted an eighteen-month study using ab initio student pilots as participants. This study applied a Federal Aviation Administration (FAA) approved, Part 142, flight-training curriculum that included 60% flight training device (FTD) use. Researchers identified five causal factors that warranted further investigation. The causal factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Ten studies relate to training proficiency. This category includes five studies on VFR or IFR training (McDermott, 2005;Reweti, 2014;Reweti et al, 2017;Taylor et al, 2004;Taylor et al, 2005); three studies on ab initio pilot training (Macchiarella et al, 2006(Macchiarella et al, , 2008McLean et al, 2016;Roessingh, 2005); one study on CRM training (Nullmeyer et al, 2006); and one study on skill decay and re-acquisition training (Svensson et al, 2013). Eight studies investigate motion (Bürki-Cohen & Go, 2005;Bürki-Cohen et al, 2007;Grundy et al, 2016;Mulder et al, 2013;Nieuwenhuizen et al, 2013;Pool et al, 2016;Sparko et al, 2010;Zaal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies relate to training proficiency. This category includes five studies on VFR or IFR training (McDermott, 2005;Reweti, 2014;Reweti et al, 2017;Taylor et al, 2004;Taylor et al, 2005); three studies on ab initio pilot training (Macchiarella et al, 2006(Macchiarella et al, , 2008McLean et al, 2016;Roessingh, 2005); one study on CRM training (Nullmeyer et al, 2006); and one study on skill decay and re-acquisition training (Svensson et al, 2013). Eight studies investigate motion (Bürki-Cohen & Go, 2005;Bürki-Cohen et al, 2007;Grundy et al, 2016;Mulder et al, 2013;Nieuwenhuizen et al, 2013;Pool et al, 2016;Sparko et al, 2010;Zaal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…(See Table B2 for the complete data set.) Macchiarella et al (2006Macchiarella et al ( , 2008 reported 52 participants but only collected data from 38. dc Svensson et al (2013) reported 51 participants but only 6 participants in the transfer study.…”
Section: Summary Of the Findings From The Primary Studiesmentioning
confidence: 99%
See 3 more Smart Citations